Acknowledgment to Reviewers of ChemEngineering in 2020 - ChemEngineering Editorial Office (ChemEngineering, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that ChemEngineering maintains its standards for the high quality of its published papers [...]